Mallomonas decipiens sp. nov. (Synurales, Chrysophyceae)—a new unique species from Vietnam - Gusev, Evgeniy S.; Shkurina, Nataliya A.; Ignatenko, Marina E.; Huan, Phan Trong (Phytotaxa, 2026)
A new species, Mallomonas decipiens sp. nov., is described from Vietnam based on silica-scale morphology observed using scanning and transmission electron microscopy. Mallomonas decipiens belongs to section Papillosae and is most similar to M. korshikovii, M. delanciana and M. verrucosa. Scales of M. decipiens have a shallow elongated dome, which is recessed from the distal margin, papillae on the dome and anterior flanges, and the open reticulation on the shield. Bristles of the newly described species are short, with a bifurcated apex and a flattened foot. The new species has been found in eight localities in six provinces from the northern to the southern parts of Vietnam.